DASAR ADMINISTRASI DALAM PENDIDIKAN ISLAM - Mariani Mariani (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2023)
Basic administration is very important in Islamic education, because without good administration it is very difficult for Islamic education to run smoothly to achieve the expected goals, namely the formation of a Muslim personality and piety to Allah SWT. In the administrative process, the main functions are planning, organizing, actuating and controlling. Planning in the administration of Islamic education really determines the goals to be achieved by an organization in Islamic education that will be able to run smoothly if there are principles of freedom of justice and deliberation. The actuating (implementation) function is to lead, including providing motivation, directing subordinates to work with high willingness and efficiency to achieve organizational goals. Finally, the controlling (supervision) function in Islamic education is a continuous monitoring process to ensure the consistent implementation of planning, both material and spiritual. The basic principles of administration in Islamic education include faith and morals, justice and equality, deliberation and division of work and tasks.